2016
DOI: 10.1016/j.imlet.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody targeting the dimer interface of epidermal growth factor receptor (EGFR)

Abstract: Epidermal growth factor receptor (EGFR) is an attractive target for the treatment of epithelial cancers. However, EGFR antagonists have low clinical response rates and frequently induce resistance mainly caused by the hypermutation of the extracellular and intracellular domains and the heterodimerization of EGFR. Dimerization plays a key role in the activation of the EGFR family of receptors. Thus, targeting the highly conserved dimer interface of EGFR maybe an attractive strategy for improving the clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…About 70% of liver cancer cells express high levels of EGFR, whereas activated EGFR plays an important role in cell migration, which in turn lead to angiogenesis (21). Thus, inhibition of EGFR is a potential treatment of cancer (22,23). We found that HCV-E2 increased the expression of miR-490 in MC-derived exosomes and recipient HCC cells, thereby reducing the activity of EGFR/AKT/ERK1/2 pathway and inhibiting the migration of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…About 70% of liver cancer cells express high levels of EGFR, whereas activated EGFR plays an important role in cell migration, which in turn lead to angiogenesis (21). Thus, inhibition of EGFR is a potential treatment of cancer (22,23). We found that HCV-E2 increased the expression of miR-490 in MC-derived exosomes and recipient HCC cells, thereby reducing the activity of EGFR/AKT/ERK1/2 pathway and inhibiting the migration of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is a 170-kDa protein consisting of 3 domains: an extracellular domain that binds ligands, a transmembrane domain, and an intracellular domain with tyrosine kinase activity [ 24 ]. EGF binds with EGFR and induces tyrosine kinase phosphorylation of its intracellular domain [ 25 ], which then recruits effector proteins to its phosphorylated C-terminal domain and activates effector protein-mediated signal pathways that regulate proliferation, survival, differentiation, migration, invasion, and injury repair of cells [ 26 ]. EGFR is expressed in many malignant tumor cell types [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that approximately 70% of ovarian cancer cells express high levels of epidermal growth factor receptor (EGFR) and the involvement of this receptor in angiogenesis and metastasis processes, the inhibition of this receptor could offer a potential treatment for ovarian cancer [153,154]. Macrophages that are activated by weakly induced apoptosis from the TNF family cytokine (TWEAK) [155] produce exosomes that contain some more microRNA-7 (miR-7) relative to macrophages that are activated commonly.…”
Section: Inhibition Of Metastasis Migration and Proliferation In Tumo...mentioning
confidence: 99%